Balance assessment with decreased base of support for children with disabilities - Guilherme M. Cesar; Madison Giebler; Thad W. Buster; Judith M. Burnfield (Clinical and Experimental Pediatrics)
Background Children’s ability to achieve an appropriate motor development is largely associated with their capacity to control balance. Furthermore, accomplishing balance tasks with a narrowed base of support is a necessary precursor to engaging in everyday functional activities and developing more complex balance abilities. Purpose To investigate the relationship between the tandem stance (TS) and the single-limb stance (SLS) items of the Pediatric Balance Scale (PBS) assessment tool with the PBS total score in children with impaired balance. Methods Forty-two children (22 with neurological disabilities, 10.7±3.1 years; 20 typically developing [TD], 8.3±2.7 years) performed all 14 PBS items. Linear regressions separately determined the impact of TS and SLS on total PBS score in both groups. Bland-Altman plots expressed agreement between the balance measurements. Results For children with disabilities, only the SLS entered the model, explaining 64.5% of the variance in total PBS score. A high level of agreement was observed between the SLS and total PBS scores. For TD children, only the TS entered the model, explaining 45.2% of the variance in the total PBS score. A high level of agreement was observed between the TS and total PBS scores. Conclusion Our findings support the practical and efficient use of a single balance task to assess balance ability in children with disabilities.